Of Menelaah Spiritual Mistisisme Tasawuf Imam Al Ghazali dan Ibnu Arabi - Anrivika, Gerry Ismail; Rahman, Mohammad Taufiq (Integritas Terbuka: Peace and Interfaith Studies, 2024)
This study aims to examine the differences in the spiritual mysticism of Sufism between Imam al-Ghazali and Ibn Arabi from their respective perspectives. Using a qualitative approach with a literature review method, this research analyzes the concepts, practices, and manifestations of Sufism in both religious and social contexts. Data were collected through an in-depth literature study of the thoughts of these two figures. The findings of the study show that Imam al-Ghazali's understanding of Sufism focuses more on morality and the purification of the soul, while Ibn Arabi places greater emphasis on the metaphysical aspect and wahdat al-wujud (unity of being). The thoughts of both figures were also influenced by Greek philosophy, which led to differences in the style of their spiritual views. This study contributes to a deeper understanding of the variations in Sufi thought and its relevance in the modern context.